Remote electronic voting: search for legislative formalization - Elena N. Bosova; Dmitry A. Reut (Pravoprimenenie, 2019)
The subject. Normative acts which are the legal basis for remote e-voting conducted as an experiment on a single voting day on September 8, 2019 in Russia. New electoral technologies, including positive and negative forecasts of the success and necessity of this vote, are also in the focus of research.The purpose of the study is to consider the state of the legal framework for conducting the remote electronic voting experiment in the Russian Federation and its further development. We are aimed also to find out what laws have become the basis for remote electronic voting, what is the degree of by-laws regulation.The methodology. The main research method is comparative legal method, which allows revealing the concept of the remote electronic voting experiment and its procedural and technological features, as well as such general scientific research methods as analysis, synthesis, induction and deduction.The main results of the study and their scope. The concept of the experiment, its procedural and technological features are revealed. Skeptics say about the potential danger of this system in the scope of data storage and transmission. One can object to this by referring to the widespread use of Internet banking for transactions, as well as to the demand for the Moscow portal of public services among millions of people. With a high degree of probability it can be concluded that the remote method of voting will be in demand mainly among voters who are regular users of the Internet.  Empowerment monitor the process of electronic voting will increase people's trust in this form of participation in the elections will have a fruitful impact on strengthening the institution of social control, which in the preparation for the experiment on remote electronic voting organized wide expert and public discussion, with participation of representatives of public and human rights organizations are not subjects of the electoral process. Skeptics say about the potential danger of this system in terms of data storage and transmission. Meanwhile, Internet resources are subject to similar threats. used by millions of people for transactions (Internet banking, Internet portal of public services). With a high degree of probability it can be concluded that the remote method of voting will be in demand mainly among voters who are regular users of the Internet.  The expansion of opportunities for monitoring the process of electronic voting will help to increase people's confidence in this form of participation in elections, will have a fruitful impact on the qualitative strengthening of the institution of public control. The necessary provision of success is  proper preparation for the experiment on remote electronic voting, including large-format expert and public discussion, in which representatives of public and human rights organizations that are not subjects of the electoral process are involved. The world experience of a similar procedure shows contradictory results, but in the future it is hardly possible to abandon the technologies that contribute to the democratization of the electoral process. The electronic voting procedure in Russia, regulated by federal laws and by-laws regulation after the elections of 8 September 2019, will be improved taking into account the experience gained.Conclusions. The experiment of remote electronic voting in Russia will contribute to the development of the electoral process. Suggestions of this study can contribute to the development of the electoral legislation of the Russian Federation.